Prevalence, Etiological Patterns and Factors Associated with Bacteraemia Among Febrile Children with Sickle Cell Anaemia in Jinja Regional Referral Hospital, Uganda - Haji Ali AM; Abdi AA; Said AI; Omar AM; Salad AH; Namukasa F; Ndeezi G; Nduwimana M (Infection and Drug Resistance)
Abdifatah Muhuyadin Haji Ali,1 Awil Abdulkadir Abdi,2 Amatarahman Ibrahim Said,1 Abdirizak Mohamed Omar,1 Abdirahman Hassan Salad,1 Faith Namukasa,1 Grace Ndeezi,1 Martin Nduwimana1 1Department of Pediatrics, Faculty of Clinical Medicine and Dentistry, Kampala International University, Bushenyi, Uganda; 2Department of Internal Medicine, Faculty of Clinical Medicine and Dentistry, Kampala International University, Bushenyi, UgandaCorrespondence: Awil Abdulkadir Abdi, Department of Internal Medicine, Faculty of Clinical Medicine and Dentistry, Kampala International University, Bushenyi, Uganda, Email awil6263@gmail.comBackground: Children with sickle cell anemia (SCA) are highly susceptible to bacterial infections. While studies in Sub-Saharan Africa have explored the prevalence and causes of bacteremia in SCA, no such data exist from Uganda. This study aimed to determine the prevalence, bacterial causes, and associated factors of bacteremia among febrile children with SCA at Jinja Regional Referral Hospital (JRRH).Methods: We conducted a cross-sectional study among febrile children ≤ 18 years with confirmed SCA at JRRH. Data on sociodemographic, clinical, and laboratory variables were collected from caregivers and medical records. Blood samples were cultured using the BACTEC FX200 system and sensitivity for Kirby-Bauer disk diffusion. Descriptive statistics reported prevalence and etiology. Binary logistic regression was used to identify factors associated with bacteraemia, using SPSS v26. Statistical significance was set at p < 0.05.Results: Of the 209 febrile children enrolled, 114 (54.5%) were male and 116 (55.5%) were under five years. Bacteremia was confirmed in 44 patients (21.1%). The most frequent isolate was Staphylococcus aureus (25/44, 56.8%), followed by Escherichia coli (8/44, 18.2%), Klebsiella pneumoniae (3/44, 6.8%), and Haemophilus influenzae (3/44, 6.8%). All isolates were resistant to gentamicin, ampicillin, penicillin, and ofloxacin. S. aureus showed good sensitivity to cloxacillin. Factors associated with bacteremia were low maternal education (aOR = 1.098; 95% CI: 1.007– 1.197; p = 0.037), tachycardia (aOR = 1.116; 95% CI: 1.027– 1.213; p = 0.010) and neutrophilia (aOR = 1.536; 95% CI: 1.363– 1.731; p < 0.001).Conclusion: Bacteremia was common among febrile children with SCA, with Staphylococcus aureus as the leading isolate. Blood cultures should be prioritized. Ampicillin and gentamicin were ineffective, whereas cloxacillin, cefotaxime, and other antibiotics with demonstrated sensitivity are recommended as empiric alternatives.Keywords: sickle cell anemia, Staphylococcus aureus, Escherichia coli, bacteremia, prevalence, Uganda